Impact of Coal Mining Companies on Community Life in Tanjung Raman Village, Taba Penanjung District, Bengkulu Central Regency - Alex Abdu Chalik; Hilal Ramdhani; Riska Sarofah; Faisal Fadilla Noorikhsan (Universitas Medan Area, 2022)
This study aims to reveal the impact of coal mining companies on people's lives in Tanjung Raman Village, Taba Penanjung District, Central Bengkulu Regency, Bengkulu Province. The problems of this research focus on four main aspects of people's lives affected by coal mining, namely the physical environment, socio-economic community, public health, and social psychological community. This study uses a qualitative approach about four main aspects of people's lives affected by coal mining. Data collection techniques using interviews, observation, and documentation. The results of the study show that there have been four impacts of coal mining companies on people's lives. This has an impact on the majority of residents using dug wells to meet their daily water needs; the occurrence of changes in employment opportunities, namely working as coal extraction in the Kemumu River and changes in work patterns from farming to coal collectors in the river; public health also declines such as the emergence of skin diseases; as well as the accumulation of community disillusionment that has been buried for a long time, which can lead to acts of violence. The results of this study conclude that there are four impacts of the company on people's lives which include the impact of the physical environment, socio-economic, public health and socio-psychological conditions of the community.